A Study of the Effect of Asana and Pranayama Training on Flexibility, Cardiovascular Strength - Dr. Urvashi D. Patel; Dr. Vishnubhai D. Chaudhari (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The purpose of this research study was to study the effect of asana and pranayama training on flexibility, core strength. In this research study. The student Madhav University, Pindwara, Rajasthan were selected. In this research study, 40 student Girls in the age group of 17 to 20 years were randomly selected. In this research study, a total of 40 female students were divided into two groups, 20 male female students as the Asana and Pranayama group and 20 male female students as the control group. The standard of measurement was flexibility was measured by seat and reach test and elemental strength was measured by peak flowmeter. One way analysis of covariance (One Way Analysis of covariance) test was applied to find out the effect of posture and pranayama on flexibility, core strength and significance was tested at 0.05 level. The findings of which were seen as follows. A twelve-week asana and pranayama training program of Paddhattisara showed improvements in flexibility and core strength in selected subjects.